Prevalence of intestinal parasitic infection of kindergarten children - Maharjan, R; Timilshina, M; Shakya, R; Bhattarai, S; Bhattarai, S; Gurung, P (International Journal of Infection and Microbiology, 2013)
INTRODUCTION: Intestinal parasitic infections are the major public health problems of Nepal. Apart from causing mortality and morbidity, infection with intestinal parasites has been associated with stunting of linear growth, physical weakness and low educational achievement in school children. The drinking water is considered as the major cause for parasitic infection. This study aims to determine the prevalence of parasitic infection among the children visiting kindergarten of the Kathmandu, Khusibhu area. MATERIALS AND METHODS: Cross sectional study was done in randomly selected Kindergarten of Khusibhu area. A total of 101 samples were examined. The study was focused in isolating intestinal parasites using normal saline and iodine wet mount method. Both macroscopic and microscopic studies were performed. RESULTS: Among the samples 45.5% (n=46) showed parasitic infection in which the Giardia lambia infection was found the highest 56.5% (n=26) and infection with Ascaris lumbricoides was found lowest 8.7% (n=4). Infection rate was found to be high in children drinking filtered water than among those drinking boiled and filtered water. CONCLUSION: The prevalence of parasitic infection in children is mainly associated with hygiene and food habit of the children. Hence good education about the hygienic practice helps in the prevention of the infection. DOI: http://dx.doi.org/10.3126/ijim.v2i3.8205 Int J Infect Microbiol 2013;2(3):111-113